2018
DOI: 10.1016/bs.acr.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and Exosomes: A Novel Target in Cancer Biology and Therapy

Abstract: Exosomes are secreted extracellular vesicles (EVs) that carry micro RNAs and other factors to reprogram cancer cells and tissues affected by cancer. Exosomes are exchanged between cancer cells and other tissues, often to prepare a premetastatic niche, escape immune surveillance, or spread multidrug resistance. Only a few studies investigated the function of lipids in exosomes, although their lipid composition is different from that of the secreting cells. Ceramide is one of the lipids critical for exosome form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 207 publications
(260 reference statements)
1
80
0
1
Order By: Relevance
“…These differences were detected in CER[NS] and CER[NDS] ceramides, the relative levels of which increased and decreased, respectively, in keratinocytes, while the corresponding levels of these ceramide classes were unchanged in the fibroblasts of psoriatic patients. It has been shown that ceramide is critical for exosome formation and increased ceramides generation led to induction of exosome secretion [38]. Exosomes are cell-derived membrane vesicles that are secreted by cells in order to remove proteins and lipids, and release them in the extracellular space [39].…”
Section: Discussionmentioning
confidence: 99%
“…These differences were detected in CER[NS] and CER[NDS] ceramides, the relative levels of which increased and decreased, respectively, in keratinocytes, while the corresponding levels of these ceramide classes were unchanged in the fibroblasts of psoriatic patients. It has been shown that ceramide is critical for exosome formation and increased ceramides generation led to induction of exosome secretion [38]. Exosomes are cell-derived membrane vesicles that are secreted by cells in order to remove proteins and lipids, and release them in the extracellular space [39].…”
Section: Discussionmentioning
confidence: 99%
“…Both endogenous derived and exogenous administrated D-ribose induces the activation of NLRP3 and secretion of IL-1β, which further lead podocyte injury, chronic sterile glomerular inflammation, and glomerular sclerosis. Ceramide is required for extracellular vesicles formation, secretion, and function such as delivery of effector molecules (Elsherbini and Bieberich, 2018). Inhibition of lysosomal ceramide decreases extracellular vesicle secretion, thereby reducing the transport of NLRP3 inflammatory cytokines from the podocytes to exercise their function in initiating glomerular injury and renal fibrosis.…”
Section: Renal Fibrosismentioning
confidence: 99%
“…This is not so surprising since the composition of plasma differs considerably from the composition of cells or tissue. Moreover, ceramide in the peripheral plasma is mainly associated with extracellular vesicles, and since MM is associated with higher levels of circulating EVs derived from the MM cells themselves, the alteration in the plasma lipid profile might be the result of a higher concentration of EVs in the plasma [16][17][18][19]. Other studies have also performed lipidomic analysis on patient plasma to discover potential biomarkers for solid tumors, such as lung, breast, pancreas, ovarian, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%